The global anti-corruption regime: the case of Papua New Guinea - Harris, Hannah (The law of financial crime, 2019)
Setting the stage : corruption and the global anti-corruption regime -- The United Nations Convention against Corruption : the primary tool of the global anti-corruption regime -- Corruption and anti-corruption in the South Pacific context : key actors, values, and interests -- The case study of Papua New Guinea -- Experience from the field : insight into the implementation and enforcement of the United Nations Convention against Corruption in Papua New Guinea -- Seeking answers : understanding the United Nations Convention against Corruption and its role in Papua New Guinea -- The final question : possibilities for the future and concluding remarks